Biomonitoring of firefighters occupational exposure to polycyclic aromatic hydrocarbons during the 2014 hot season - Oliveira, M. (2018)
Human biomonitoring is an important tool in environmental medicine that is used to assess the level of internal exposure to environmental pollutants. Firefighters are one of the most exposed and least studied occupations. During fire suppression, firefighters are heavily exposed to a wide range of chemicals.  Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants that are considered as the largest known group of carcinogens due to their cytotoxic and mutagenic properties (IARC 2010, WHO 2013). Smoke and ashes released during a fire are important sources of PAHs. Firefighters can be also exposed to PAHs through smoking, via polluted ambient air, water, soil, and through consumption of food.  Metabolites of PAHs (OH-PAHs), such as 1-hydroxynaphthalene (1OHNapt), 1-hydroxyacenaphthene(1OHAce), 1-hydroxypyrene (1OHPy) and 3-hydroxybenzo[a]pyrene (3OHB[a]P) have been used as biological markers for measurements of human internal exposure to PAHs.  The present work aims to quantify the urinary metabolites of PAHs, namely 1OHNapt, 1OHAce, 1OHPy and 3OHB[a]P in study population of firefighters. Firemen exposed to fires that occurred during 2014 season were asked to fill a post-fire questionnaire and to collect urinary samples. A control study population group was selected to collect samples of urines during the pre-fires season (winter). Among all participating firemen only healthy no-smoking subjects were considered. OH-PAHs were analysed by high-performance liquid chromatography with fluorescence detection